2019
DOI: 10.1002/mop.32192
|View full text |Cite
|
Sign up to set email alerts
|

Thickness effects on the dielectric dispersion and optical conductivity parameters of CuO thin films

Abstract: In this article, the effect of film thickness on the structural, optical, dielectric, and optical conductivity parameters of CuO thin films are reported. CuO thin films which are prepared by the physical vapor deposition technique under vacuum pressure of 10−5 mbar with various thicknesses in the range of 50 to 1000 nm are observed to exhibit amorphous nature of growth. The values of the energy bands gaps, the spectral response of the dielectric constant and of the optical conductivity parameters are highly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…For doped and pure Fe2O3 films, it can be observed that the extinction coefficient decrease in the doping case and has smaller values as the doping increases. The optical conductivity of the prepared samples was calculated using the relation [22,23]:…”
Section: Optical Characterizationmentioning
confidence: 99%
“…For doped and pure Fe2O3 films, it can be observed that the extinction coefficient decrease in the doping case and has smaller values as the doping increases. The optical conductivity of the prepared samples was calculated using the relation [22,23]:…”
Section: Optical Characterizationmentioning
confidence: 99%